Short communication paper: " strengthening continuing nursing education: a comprehensive module using moocs for effective risk communication in global health emergencies" - Aung, Khin Thandar; Mohd Ali, Noor Azizah; Musa@ Mohd Zaid, Muniyati; Shaharzan, Nurul Jannah; Abdul Razak, Rafiza; Mohamad Nazry, Nor Nazrina (Global Academic Excellence (M) Sdn Bhd, 2024)
This study develops an innovative Massive Open Online Course (MOOC) module specifically designed for continuing nursing education, considering the critical need for efficient healthcare risk communication in the context of global health emergencies. The study utilised Thiagarajan's 4D development model, which was modified into a 3D model consisting of the stages: define, design, and develop. Through a comprehensive literature analysis, the study attempted to identify variable-risk communication strategies that are crucial for successfully handling the always-evolving complexity of health emergencies. A mixed-method approach was utilised to evaluate the readiness among nurses for learning through MOOCs, hence guiding the design and development processes. By employing rigorous literature reviews and focus group discussions, researchers identified and validated crucial information, which ultimately resulted in the development of a MOOC course on the IIUM iTtaleem platform. The developed MOOC module was thoroughly examined by subject-matter experts to ensure its accuracy. The pilot test conducted with SASMEC nurses revealed a notable improvement in the participants' understanding and confidence regarding risk communication. The module's interactive elements, such as virtual simulations and case studies, were praised for offering hands-on learning opportunities. The result of the research is a MOOC module that can be accessed worldwide, containing video lectures, quizzes, and virtual scenarios. The dissemination of guidelines for integration into nursing education programmes has highlighted its capacity to strengthen healthcare systems in the face of global health concerns. Future intentions include implementing multilingual translations and partnering with international nursing organisations to guarantee ongoing relevance and influence in the dynamic field of global health emergencies.